Social worker's attitudes to poverty and the poor - Becker, Saul (1987)
Field social workers are in daily working contact with the poor and deprived. In Britain as many as nine out of ten users of social work services are claimants of social security; over half are dependent on means tested social assistance. Most referrals to social workers are for benefit and housing problems.